La gestión del currículo diversificado en dos instituciones educativas de Ventanilla, Región Callao - Jaramillo Castillo, Raúl (2010)
This simple research descriptive report of diagnosis tries to determine how the diversified management curriculum is being performed in “Nuestra Señora de Belén” and “Consorcio Educativo AVHALDIM S.A.” secondary educational institutions according to the design, development and curriculum evaluation, all them as to the diversification of competences, skills, knowledge and attitudes, components of the National CurriculumDesign (DCN). The study was done in 2009; the sample was represented by 83 teachers, selected in a intentional way. Questionnaire was applied with the technique of the survey. The results report that the diversified management curriculums in both educational institutions are being held in the correct way. This means that the curricular management diversification considers the design, development and curriculum evaluation, constituting the teacher’s pedagogical work in a systematic way to the needs and interests of the students coherent to the National Curriculum Design DCN, regional and local orientation.